Efektivitas Cooperative Learning dalam Pembelajaran Bahasa Arab untuk Meningkatkan Kemampuan Berbahasa Mahasiswa - Mira Ulfa (Ameena Journal, 2026)
Arabic language learning requires methods that can improve students’ language skills actively and communicatively. One of the methods widely used in modern learning is cooperative learning because it emphasizes collaboration and interaction among students during the learning process. However, in practice, students’ language abilities in Arabic learning have not yet developed optimally, so a study on the effectiveness of cooperative learning in improving students’ language skills is needed. This study aims to analyze the effectiveness of cooperative learning in Arabic language learning and examine its influence on improving students’ language abilities. This study employed a library research method by collecting various data sources such as books, scientific journals, articles, and previous studies relevant to the research topic. The data were analyzed descriptively through the processes of collecting, classifying, understanding, and drawing conclusions based on the reviewed sources. The results of the study indicate that cooperative learning has a positive influence on improving students’ language abilities, especially in speaking, reading, listening, and writing skills. In addition, cooperative learning can also increase students’ learning motivation, participation, collaboration, and self-confidence in using Arabic during the learning process. The success of this method is influenced by the lecturer’s role in managing groups, the use of appropriate learning strategies, and students’ active involvement in learning activities. This study contributes to the development of more active, communicative, and collaborative Arabic learning methods to improve students’ language abilities optimally.